ANALISIS PENGARUH BELANJA MODAL TERHADAP PDRB PER KAPITA DAN IMPLIKASINYA PADA KUALITAS PEMBANGUNAN MANUSIA - , Rizki Amalia A.; , Dr. Eko Suwardi, M.Sc., CMA., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to examine the effect of Capital Expenditures to the GRDP per Capita and its implications on the Quality of Human Development at districts and cities throughout Indonesia. Samples in this study were 429 areas consist of 344 districts and 85 cities. The method used was panel data regression using Eviews 6.0 software with a fixed effect estimation method. The study also tested the effect of mediation between Capital Expenditure on Human Development Index with a GRDP per Capita as a mediating variable. The result shows that the Capital Expenditures have positive and significant effect on GRDP per Capita, the Capital Expenditures indicated have no positive and significant effect on Human Development Quality, and GRDP per Capita have no positive and significant effect as a mediating variable between Capital Expenditure and Human Development Quality.